Desain Dan Implementasi Sistem Presensi Berbasis Rfid Untuk Dosen Dan Mahasiswa - Fazrur Ridlo Robbie; Achmad Agus Athok Miftachuddin (Kampus Akademik Publiser, 2025)
Attendance management at Universitas KH. A. Wahab Hasbullah still relies on manual and mobile-based methods (Asdos), which are inefficient and prone to errors. This study aims to design and implement a Radio Frequency Identification (RFID)-based attendance system for lecturers and students to improve efficiency, accuracy, and automation. The research applied the System Development Life Cycle (SDLC) Waterfall model, covering requirements analysis, system design, implementation using RFID Reader 4100 Proximity Type USB, PVC EM4100/TK4100 cards, PHP CodeIgniter, and MySQL, as well as Black Box testing. The system was tested in two classes with 2–3 lecturers and 20–40 students. Results showed that the system records attendance in less than one second, increases efficiency by 70% compared to manual methods, and achieves 98% accuracy through RFID authentication. Automatic notifications support lecturers in managing teaching time, and attendance reports comply with official academic formats. This system proves effective, accurate, and user-friendly, offering a low-cost solution suitable for academic administration.